An Analysis on the Publishing Process and Co-occurrence Structure of Articles in the Field of Knowledge Tree - Reza Dehkhodaei; Mazyar Karamali; Mohammad Mohammadian; Mohammadkarim Bahadori; Mohsen Abbasifarajzadeh (Tehran University of Medical Sciences, 2024)
Background and Aim: Considering the importance of knowledge management in the current era and the emphasis on the implementation of knowledge management in the health system in the knowledge management system of the Ministry of Health, Treatment and Medical Education, and since it is one of the first steps in the implementation of knowledge management, Drawing the knowledge tree of the organization, the purpose of the current research is to review the process of publishing the knowledge tree and examine it in the field of health. Materials and Methods: The current research is a type of applied and descriptive review study that was carried out with the method of scientometrics and co-occurrence analysis of keywords. For this purpose, the term "Knowledge tree" OR "knowledge trees" was searched in Scopus reference database. For data analysis, the analyzes provided by the database itself were used, and VOSviewer software was used to visualize the data. Results: The growth of scientific productions related to the field of the tree of knowledge in general in the mentioned base has started since 1979 and has had a growing trend until 2023. In the field of knowledge tree, among the authors Yang, Y, among the organizations, machine intelligence institute, iona college, and among the countries, China, America, and England have been at the top of the most productive in this field. Among the subjects, the most related articles are primarily related to the field of computer science (32.2 percent) and then to the field of engineering (22.1 percent) and mathematics (10.1 percent), which is significant. that medicine is in the sixth place and this is a sign of the weakness of producing resources in this field and the clustering resulting from the co-occurrence of keywords led to the identification of five clusters respectively with the titles of data mining and information processing, artificial intelligence and expert systems. , knowledge structure and decision support systems, semantics and knowledge representation, and finally learning and teaching systems. Conclusion: The study of the thematic structure of scientific productions in the field of Knowledge Tree showed that the field of health has a weakness in the production of resources in this field. Therefore, it is necessary for future researches to pay special attention to the development and explanation of this concept and modeling its drawing, especially in the health system, in order to identify and prevent diseases.